Evidence of ferroelectric behaviour in CaCu3Ti4O12 thin films deposited by RF-sputtering - Foschini, Cesar R. [UNESP]; Hangai, Bruno [UNESP]; Ortega, Pedro Paulo [UNESP]; Longo, Elson [UNESP]; Cilense, Mário [UNESP]; Simões, Alexandre Z. [UNESP] (National Library of Serbia, 2019)
The origin of abnormal ferroelectric and unusual piezoelectricity in the polycrystalline CaCu3Ti4O12 (CCTO) thin films deposited by RF-sputtering on Pt/Ti/SiO2/Si (100) substrates was explored. The CCTO thin films, deposited at room temperature followed by annealing at 600 °C for 2 h in a conventional furnace, have a cubic structure with lattice parameter a = 7.379 ± 0.001 Å and without any secondary phases. No polarization loss up to 1010 switching cycles, with a switched polarization ∆P of 30 µC/cm2 measured at 400 kV/cm was evidenced. The piezoelectric coefficient investigated by piezoresponse force microscopy (PFM) was approximately 9.0 pm/V. This may be the very first example of exploring the origin of ferroelectric behaviour for a material that possesses space charge polarization with highly resistive grain boundaries in the polycrystalline state.
Keywords: Calcium copper titanate; CCTO; Ferroelectricity; RF-sputtering; Thin films